Peran Media Sosial Instagram Dalam Upaya Menjaga Eksistensi Bahasa Bali - Gusti Nyoman Mastini; Ni Ketut Kantriani; Ni Wayan Arini (Jayapangus Press, 2021)
Language is one of the most important needs in social life. Balinese as a mother tongue is one of the identities and ancestral heritage that must be maintained and maintained properly. Existence can also be known by one word, namely existence. where existence is meant by the response from people around us which proves that our existence is recognized. This paper aims to describe the role of social media Instagram in an effort to maintain the existence of the use of Balinese language. The method used in this study is a qualitative method with descriptive analysis techniques. The results show that on Instagram social media accounts such as @wikibasabali, @Bahasa_bali which contains an online dictionary of three languages ​​(Bali-Indonesian-English), virtual libraries, the use of anggah ungguhing basa, the use of Balinese in daily life, as well as on the @beluluk account which presents humor or entertainment in the form of Balinese comics, in this case Instagram social media can be one of the media that plays a role in efforts to maintain the existence of the Balinese language.